Jalinan Komunikasi antara Public Relations dan Jurnalis dalam Membangun Media Relations Bermakna (Studi Kasus: Tokopedia dan Kompas.com, Sub-Rubik: Money) - Fardhal Virgiawan Ramadhan; Rini Sudarmanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The relationship between PR and jurnalist has an important role in building sustainable media relations. This is because these two roles have a big influence in distributing information in the fields of economics, politics, social and even entertainment, lifestyle, trends, health, food, and finance. Tokopedia, as one of the largest e-Commerce in Indonesia, of course, must have a good relationship with journalist so that the news and information presented are interesting and do not affect the company's image. It is known that Tokopedia has a media relations relationship with Kompas.com, this is known from the news in the Money sub-rub. The aim of this research is to determine the relationship between PR and journalism between Tokopedia and Kompas.com in the Money sub-rub. The method used in this research is qualitative research methods with analytical descriptive research. The author will explain and analyze the relationship between PR and journalist on Tokopedia and Kompas.com. The results of this research show that for Tokopedia PR, the role of reporting information about the company will certainly be related to the company's image and reputation. Meanwhile, the role of Kompas.com journalist is not just to publish trending news but can provide and even help improve the company's image and reputation or even vice versa.